Psychological Lockdown Experiences: Downtime or an Unexpected Time for Being? - Procentese, Fortuna; Esposito, Ciro; Gonzalez Leone, Florencia; Agueli, Barbara; Arcidiacono, Caterina; Freda, Maria Francesca; Di Napoli, Immacolata (Frontiers in Psychology, 2021)
The spread of COVID-19 in Italy resulted in the implementation of a lockdown that obligated the general populace to remain at home for approximately two months. The lockdown interrupted citizens’ professional and educational activities, in addition to closing shops, offices and educational institutions. The resulting changes in people’s daily routines and activities induced unexpected changes in their thoughts, feelings and attitudes, in addition to altering their life perceptions. Consequently, the present study explores how young adults perceived their lives under lockdown during the final week of March 2020, when the reported number of daily coronavirus infections reached its peak in Italy. The research was carried out among 293 university students (234 women and 59 men) with an average age of 20.85 years old (SD=3.23). The researchers asked participants to describe the emotions, thoughts and experiences that characterized their time under lockdown. The study analyzed specific narratives related to time and space using grounded theory methodology, which was applied using Atlas 8 software, leading to the creation of 68 codes. The study organized these codes into three specific categories: confined in the present, confined in the past, and striving toward one’s goals. Finally, the researchers also created a core-category labeled “continuity of being.” The results showed that the closure of open spaces caused a division in participants’ perceptions of time continuity, with many viewing themselves as feeling fragmented and as living the present in a static and fixed way. Additionally, participants also saw the present as being discontinuous from the past, while, simultaneously, projecting toward the future and the changes it might bring. Finally, this study examined further implications surrounding individual projecting among young people in greater depth.